Pengaruh Tingkat Implementasi IFRS dan Kualitas Audit Terhadap Pengakuan Kerugian Tepat Waktu - Meliantha Olivia; Putri Nurmala (Universitas Mataram, 2020)
This study aims to examine the impact of IFRS implementation and audit quality which represented by client importance on timely loss recognition.This study uses profitability as control variable. This research was conducted in the manufacture companies except BUMN and financial companies which listed in Indonesia Stock Exchange in 2012-2016.This research study used a quantitative research with secondary data. Population in this research are 151 companies, the sample withdrawal method using purposive sampling technique to obtain the number of samples, are 18 companies with 5 years of observation data as much as 90 data. Research data in the form of annual financial reports that published by BEI or Indonesian Stock. Exchange. The data analysis technique that used is multiple linear analysis with the help of SPSS program ver. 21. Based on the result of testing the hypothesis, showed that the implementation of IFRS have a significant impact on timely loss recognition, audit quality as a independent variableand profitability as a control variable doesn’t show any significant impact on timely loss recognition.